The heat transfer model for VGF technique with skull layer for halide crystal growth - Taranyuk, V.I.; Gektin, A.V.; Kolesnikov, A.V.; Kalaev, V.V. (Functional Materials, 2014)
The work is devoted to the investigation of the key parameters for reproducible skull technique of NaI based crystals. Combination of math simulation (CGSim software) with experimental measurements of the temperature distribution during the raw material heating, melting stage and later crystallization gave not only approval of the methodology but allowed to grow scintillation crystal with the same performance as typical for single crystals. The obtained results are applicable for the skull layer thickness minimization, melting and crystallization stages verification and estimation of the gradient for proper convection and crystal homogenization. As result the medium size (250× 180× 45 mm³) NaI crystals were obtained.